**Who are the experts?**Our certified Educators are actual professors, teachers, and scholars who usage their scholastic expertise come tackle her toughest questions. Educators go v a rigorous applications process, and also every answer they submit is the review by our in-house editorial team.

You are watching: What is a solution of x^2+6x=-5

In identify the factorization, the is a an excellent trick to recognize that as soon as the coefficient the the x^2 is without doubt one (as the is in this case), fixing for the two determinants is much easier.

Basically, what 2 numbers, when multiplied, equal positive 5, but when added together, equal an adverse 6?

...

Start your **48-hour free trial** to unlock this answer and also thousands more. Gain tastecraftedmcd.com ad-free and also cancel anytime.

In identify the factorization, that is a an excellent trick to know that as soon as the coefficient of the x^2 is indeed one (as it is in this case), resolving for the two factors is much easier.

Basically, what two numbers, once multiplied, equal confident 5, but when added together, equal an unfavorable 6?

The just possibility is -1 and also -5. Thus (x-1), (x-5)

To check your answer, you deserve to use the FOIL technique of multiplying your two determinants (first, outside, inside, last), come arrive back to the original equation:

First = x times x equates to x^2.

Outside = x time -5 equals -5x.

Inside = -1 times x equals -x.

Last = -1 times -5 amounts to 5.

Combined climate you have x^2 -5x -x +5, streamlined to x^2-6x+5.

authorized by tastecraftedmcd.com Editorial Team

Tushar Chandra

Educator due to the fact that 2010

12,621 answers

| Certified education

page Citation

Share attach

The systems of a quadratic equation ax^2 + bx + c = 0 is given by `(-b+-sqrt(b^2-4ac))/(2*a)`

In the problem, the solution of the equation x^2 - 6x + 5 = 0 needs to be determined. Using the formula offered earlier, a = 1, b = -6 and also c = 5.

The root of the equation are `(6 +-sqrt(36-20))/(2*1) = (6+-4)/2`

The roots are 5 and 1.

It is also possible to factorize the expression x^2 - 6x + 5 to determine the root of the equation.

x^2 - 6x + 5 = 0

=> x^2 - 5x - x + 5 = 0

=> x(x - 5) - 1(x - 5) = 0

=> (x - 1)(x - 5) = 0

=> x = 1 and x = 5

Again, the same roots room obtained.

See more: Image Result For How To Make A Dwarfs Hat, Snow White, Dwarfs Disney Hats (1968

**The root of the equation x^2 - 6x + 5 = 0 are 1 and 5**

authorized by tastecraftedmcd.com Editorial Team

### Ask a Question

ask a inquirySubmit inquiry

### Popular Questions

view all

## Related Questions

Browse everyMath

recent answer posted December 24, 2010 at 5:33:17 to be

resolve x^2 + 7x +9 = 0 utilizing the quadratic formula

2 educator answers

Math

latest answer post August 23, 2014 in ~ 2:29:29 afternoon

settle the equation x^3-3x^2-6x+8 = 0

1 education answer

Math

latest answer posted August 18, 2014 in ~ 3:56:18 to be

resolve the equation : 2*sin^2 x + cos x - 1 = 0

3 education answers

Math

latest answer posted August 23, 2013 at 8:38:37 am

solve by using the quadratic formula. Placed answer in specific value, simplestradical form.3x^2 + 6x + 2 = 0

2 education answers

Math

recent answer post January 04, 2011 in ~ 11:55:49 am

fix using the quadratic formula: 3x^2 -5x -4 = 0

3 education answers

tastecraftedmcd.com will help you with any book or any question. Our summaries and also analyses are written by experts, and your questions are reply by genuine teachers. sign up with tastecraftedmcd.com

use to be an education

### Recommended

### More

©2021 tastecraftedmcd.com, Inc. All legal rights Reserved